Mobile phone addiction and negative emotions: an empirical study among adolescents in Jiangxi Province - Luo, Jin; Cai, Guanqing; Zu, Xiaofang; Huang, Qiming; Cao, Qing (Frontiers in Psychiatry, 2025)
BackgroundThe relationship between mobile phone addiction and negative affect among adolescents is characterized by intricate interconnections. These factors have an impact on the emotional and psychological well-being of young people. While previous studies have provided preliminary insights into this relationship, further in-depth exploration and research is required to fully understand the complex mechanisms behind these relationships and to identify any group differences.MethodsThis study collected questionnaire data from 493 adolescents aged 17-22 years old in Jiangxi Province. The data were analyzed using Pearson correlation analysis, restricted cubic spline (RCS), and structural equation modelling (SEM) with the aim of exploring the mechanisms and differences in the effects of mobile phone addiction on negative emotions of different youth groups.ResultsThe findings of the study indicated notable discrepancies in mobile phone addiction by gender and place of residence. Secondly, mobile phone addiction among adolescents positively drives negative emotions. The findings revealed that negative emotions triggered by mobile phone addiction were significantly higher among rural adolescents than urban adolescents; male adolescents exhibited higher levels than female adolescents in the same place of residence. Additionally, family factors, physical exercise and psychological resilience can directly or indirectly inhibit mobile phone addiction among adolescents. Finally, adolescents’ psychological resilience can significantly alleviate the negative emotions associated with mobile phone addiction. Physical exercise and family factors can reduce the negative emotional impact of mobile phone addiction by increasing psychological resilience.ConclusionsThis study employs the relationship between mobile phone addiction and negative emotions in adolescents, reveals the complex mechanisms and group differences behind these relationships, and provides a fresh perspective for understanding the impact of mobile phone addiction on adolescents’ mental health, as well as a scientific basis for the development of effective interventions.